2017
DOI: 10.37358/rc.17.5.5624
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Glycerol in Gas Phase on Cu-Cr Mixed Oxide Catalyst Doped with Ni

Abstract: Hydrogenolysis of glycerol was conducted on catalyst of the type mixed oxide of Cu-Cr doped with NiO on g-Al2O3. The prepared catalyst was analyzed by XRD, IR and TPR. Catalytic tests were carried out on a laboratory plant in continuous flow system on a reactor equipped with heating mantle, at molar ratio of glycerol / hydrogen of 1/300, glycerol volume hourly space velocities 1000s-1, temperatures 200-220oC and pressures 3-5 bar. The main reaction products identified were propylene glycol and hydroxyacetone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…[166] Mixed oxide of Cu-Cr doped with NiO on γ-Al 2 O 3 was tested for gas phase GL hydrogenolysis at 473 K and 3-5 bar in a flow system reactor to produce 1,2-PD and HAc, as by-product. [167] In this case, the glycol selectivity was directly related to temperature and pressure increasing up to 95 % with 85 % GL conversion (at 5 bar and 493 K). [167] Nanometric Ni phosphides, in presence of citric acid, demonstrated to act as a chelating agent, proved to be a good catalyst to produce 1,2-PD under N 2 .…”
Section: Nickelmentioning
confidence: 81%
“…[166] Mixed oxide of Cu-Cr doped with NiO on γ-Al 2 O 3 was tested for gas phase GL hydrogenolysis at 473 K and 3-5 bar in a flow system reactor to produce 1,2-PD and HAc, as by-product. [167] In this case, the glycol selectivity was directly related to temperature and pressure increasing up to 95 % with 85 % GL conversion (at 5 bar and 493 K). [167] Nanometric Ni phosphides, in presence of citric acid, demonstrated to act as a chelating agent, proved to be a good catalyst to produce 1,2-PD under N 2 .…”
Section: Nickelmentioning
confidence: 81%
“…The triacetin (TAG), acetic acid (Ac) and water (W) number of moles in the mixture were calculated from the stoichiometric relations: (6) As none of the published models provided adequate simulation results, we developed a relatively simple, homogeneous type kinetic model, considering the rate expressions of the three reactions:…”
Section: Resultsmentioning
confidence: 99%
“…By its chemical structure and physical properties, the glycerol is one of the most versatile and valuable organic compounds. Chemically, glycerol is a highly functionalized molecule used in the synthesis of more than a thousand chemical products [1][2][3][4][5][6]. A great number of processes for glycerol conversion into commodity chemicals are based on the heterogeneous catalysis (hydrogenolysis, dehydration, etherification, esterification, oxidation, reforming etc.).…”
mentioning
confidence: 99%
“…It was observed that with increasing the hydrogen molar ratio in the feed, glycerol conversion and selectivity to 1,2-PDO increased with a simultaneous decrease in the selectivity to acetol. 218 220 The SiO 2 supported Cu metal catalyst prepared by the ionexchange technique depicted an 87% yield of 1,2-PDO at 100% glycerol conversion at 255 °C and at 1.5 MPa pressure at a very higher hydrogen flow of 300 cm 3 /min. Furthermore, the catalytic activity and product selectivity were linearly increased with the specific copper surface area.…”
Section: Vapor Phase Hydrogenolysis Of Glycerolmentioning
confidence: 98%
“…However, the Ni/Al 2 O 3 catalyst was found to be very active in C–C bond breakage. It was suggested that the dehydration reaction was facilitated on the acidic sites (ZnO and Al 2 O 3 ) of the catalyst, and the hydrogenation of the intermediate was facilitated by copper metal …”
Section: Vapor Phase Hydrogenolysis Of Glycerolmentioning
confidence: 99%